Procedural Misfires of Cross-Cultural Legal Communication in the Perspective of J. Austin and J. Langshaw Austin - Korolev, Sergey (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
The article is meant to serve both theory and practice in the cross-roads area where legal theory meets linguistic philosophy. The legal perspective is represented by the famous command theory of John Austin, who is often regarded as the founding father of anglo-american branch of legal positivism. The linguistic perspective is represented by the speech acts theory elaborated by John Langshaw Austin. It is argued that the command theory is only of marginal use for any process of crosscultural legal communication. The reason behind this argument is that the command theory is grossly reductionist in its nature ("colonel – lieutenant") and cannot therefore embrace a trilateral reality of cross-cultural legal communication (speech originator – interpreter – audience). But the imperative theory may be useful if applied to "misfires" of the whole process of legal oral translation. By transforming the said trilateral reality to any dichotomy in the sense of the command theory, i.e. by bracketing together any two of the said agents and by insulating the third one- we inevitably arrive at some sort of "misfire" or even collapse of the whole procedure. Further the common view is challenged that the only source of such "misfires" lies in poor quality of interpretation. It is argued that both the speech originator and even somehow inadequate audience may share the final failure. The eventual outcome of the article may be described as an attempted synthesis of the speech acts theory of John Langshaw Austin and sociology of law as elaborated by German professor Werner Krawietz. The interdisciplinary approach to discussed "misfires" of cross-cultural legal communication resulted in formulating a series of bilateral rules, which are obligatory both for the speech originator and the interpreter if the most unacceptable "misfires" of legal oral translation are to be avoided.

Статья носит одновременно теоретический и прикладной характер. В ней предпринята попытка совместить юридическую и лингвистическую перспективу при анализе кросс – культурной юридической коммуникации. Юридическая перспектива представлена императивной теорией Джона Остина - родоначальника англо-американской версии юридического позитивизма. Лингвистическая перспектива представлена теорией речевых актов яркого представителя лингвистической философии Джона Лэнгшо Остина. Показано, что императивная теория ввиду ее крайне редукционистского характера («начальник – подчиненный») не может полностью охватить характер отношений типа «лектор – переводчик - аудитория». Все три агента являются авторами конечного продукта, т.е. удавшейся лекции. Однако императивная теория полезна при анализе различных редукционистских констелляции, в который один из трех агентов может быть выведен «за скобки» как величина, которою можно пренебречь. Критикуется распространенная точка зрения, что в неудачах юридического перевода всегда повинны переводчики. Нередко они разделяют вину с «носителем первичного текста» и даже с не вполне адекватной аудиторией. В заключении предпринята попытка конвергенции теории речевых актов Джона Лэнгшо Остина и социологии права в духе Вернера Кравица. Разработаны билатеральные правила устного перевода, которые без ущерба для процесса кросс-культурной юридической коммуникации не могут игнорировать ни носитель первичного текста, ни его переводчик.
Proceduralne pomyłki w interkulturowej komunikacji prawniczej z perspektywy J. Austina and J. Langshaw Austina
«Oсечки» кросс - культурной юридической коммуникации в перспективе Джона Остина и Джона Лэнгшо Остина